Mr Two Percent, what hope do you have? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The smart market information service (MIS) combines market prices with the farmer s savvy. We look at some success stories which have made some farmers very happy indeed, but how long can it all last?We all have at least one, locked up in the...